A noninterventional, multinational study to assess PD-L1 expression in cytological and histological lung cancer specimens - Bubendorf, Lukas; Conde, Esther; Cappuzzo, Federico; Langfort, Renata; Schildhaus, Hans-Ulrich; Votruba, Jiří; Concha-López, Ángel; Esteban-Rodriguez, Isabel; Feng, Janine; Devenport, Jenny; Boyiddle, Christine; Morris, Stefanie; et al. (Cancer cytopathology, 2020)
BACKGROUND: The diagnosis of advanced lung cancer is made with minimally invasive procedures. This often results in the availability of cytological material only for subtype determination and companion diagnostic testing, with the latter being technically and clinically validated on histological material only. Thus, the primary objective of the MO29978 clinical study was to assess programmed death ligand 1 (PD-L1) protein expression on cytology samples as surrogates for histology samples in patients with lung cancer. METHODS: Formalin-fixed, paraffin-embedded histological samples and cytological cell blocks from 190 patients were analyzed with immunohistochemical assays using the rabbit monoclonal anti-PD-L1 antibody clones SP142 and SP263. PD-L1 expression was quantified on both tumor cells (TC) and tumor-infiltrating immune cells (IC). Overall concordance, sensitivity, specificity, and accuracy, with a 1% cutoff used for both assays, were assessed for PD-L1 expression on TC and IC. RESULTS: In non-small cell lung cancer histology and cytology samples measured with the PD-L1 (SP142) antibody (n = 173), the intraclass correlation coefficients were 0.40 and 0.06 on TC and IC, respectively. With SP142 and SP263, accuracies of 74.1% for TC and 51.9% for IC and accuracies of 75.2% for TC and 61.2% for IC, respectively, were reported. CONCLUSIONS: Overall, this study has demonstrated that PD-L1 analysis on TC is feasible in cytological material, but quantification is challenging. Tumor tissue should be preferred over cell block cytology for PD-L1 immunohistochemical analysis unless laboratories have validated their cytology preanalytical approaches and demonstrated the comparability of histology and cytology for TC PD-L1 results.
Keywords: International Agencies; cytodiagnostika; monoklonální protilátky; SP142; nádory plic; Carcinoma, Non-Small-Cell Lung; ROC Curve; B7-H1 Antigen; Lung Neoplasms; cytology; Prospective Studies; SP263; imunohistochemie; Cytodiagnosis; lung cancer; lidé; Immunohistochemistry; Humans; nemalobuněčný karcinom plic; histology; antigeny CD274; programmed death ligand 1 (PD-L1); Antibodies, Monoclonal; ROC křivka; Biomarkers, Tumor; immunohistochemistry; nádorové biomarkery; mezinárodní agentury; prospektivní studie